The one-state condition : occupation and democracy in Israel/Palestine - Azoulay, Ariella; Ophir, Adi; Haran, Tal (Stanford studies in Middle Eastern and Islamic societies and cultures, 2012)
Since the start of the occupation of Palestinian territories in 1967, Israel's domination of the Palestinians has deprived an entire population of any political status or protection. But even decades on, most people speak of this rule—both in everyday political discussion and in legal and academic debates—as temporary, as a state of affairs incidental and external to the Israeli regime. In The One-State Condition, Ariella Azoulay and Adi Ophir directly challenge this belief. Looking closely at the history and contemporary formation of the ruling apparatus—the technologies and operations of the Israeli army, the General Security Services, and the legal system imposed in the Occupied Territories—Azoulay and Ophir outline the one-state condition of Israel/Palestine: the grounding principle of Israeli governance is the perpetuation of differential rule over populations of differing status. Israeli citizenship is shaped through the active denial of Palestinian citizenship and civil rights. Though many Israelis, on both political right and left, agree that the occupation constitutes a problem for Israeli democracy, few ultimately admit that Israel is no democracy or question the very structure of the Israeli regime itself. Too frequently ignored are the lasting effects of the deceptive denial of the events of 1948 and 1967, and the ways in which the resulting occupation has reinforced the sweeping militarization and recent racialization of Israeli society. Azoulay and Ophir show that acknowledgment of the one-state condition is not only a prerequisite for considering a one- or two-state solution; it is a prerequisite for advancing new ideas to move beyond the trap of this false dilemma.